2007
DOI: 10.1590/s0074-02762007000800017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a modified culture medium for Borrelia burgdorferi sensu lato

Abstract: The aim of the present study was to assess the possible use of a modified medium, prepared

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…However, after 8-10 days, further growth of the spiral form ceased and spirochetes tended to convert into different morphological forms (data not shown) as described previously 39-[42]. Multiple attempts to revert them back to spiral form were unsuccessful regardless of the use of several different media such as the original BSK-II medium 27, modified Kelly medium (MKP medium) 43, MPM medium 44, and BSK modified medium 45. In addition, several solid BSK-based media 46 and PMR-agar media 43 were similarly tested but likewise were not capable of maintaining spirochetal growth.…”
Section: Resultssupporting
confidence: 67%
“…However, after 8-10 days, further growth of the spiral form ceased and spirochetes tended to convert into different morphological forms (data not shown) as described previously 39-[42]. Multiple attempts to revert them back to spiral form were unsuccessful regardless of the use of several different media such as the original BSK-II medium 27, modified Kelly medium (MKP medium) 43, MPM medium 44, and BSK modified medium 45. In addition, several solid BSK-based media 46 and PMR-agar media 43 were similarly tested but likewise were not capable of maintaining spirochetal growth.…”
Section: Resultssupporting
confidence: 67%
“…The antimalarial activity of artemisinin might involve endoperoxide activation by free ferrous iron from hemoglobin digestion by malaria parasites ( Wells et al, 2009 ). However, the content of ferrous iron or hemoglobin is very low in the B. burgdorferi culture ( Rodriguez et al, 2007 ), so the activation of endoperoxide might not be the main mechanism of artemisinin activity against B. burgdorferi round bodies. In yeast, artemisinin impairs the membrane structure and causes depolarization of the mitochondrial membrane ( Li et al, 2005 ; Wang et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rodríguez et al (2007), after replacing CRML 1066 with 199 medium, compared the growth of different strains of Borrelia in relation to the modified Barbour-Stoenner-Kelly (BSK)-H medium with added amino acids and antibiotics and indicated that the modified medium could function as an alternative growth media for the cultivation of Borrelia strains.…”
mentioning
confidence: 99%